Grammaticalization and lexicalization: suggestions regarding the development of the Chinese change-of-state verb - Wenchao LI (Acta Linguistica Asiatica, 2018)
This paper discusses the evolution of the Chinese verb 断 (duàn ‘break’), exploring how the lexicon has transformed from being a substantive transitive verb in the past to the various functions it fulfils in contemporary Chinese: i.e. a resultative complement, an adjective, an adverb and a noun. Findings reveal that duàn was initially transitive and its intransitive function was derived during the Spring and Autumn period (772–476 BC). The two functions co-existed for the rest of the Pre-Qin period (before 221 BC). Duàn’s transition into a resultative complement began during the Eastern Han dynasty (AD 25–220), and its noun function was shaped in the Warring State period (475–221 BC). Finally, Duàn’s adjective and adverb functions are noted to begin in Middle Chinese (AD 420–1279). Although some of these transitions took place more or less simultaneously during overlapping periods, they developed via two separate paths: the process by which duàn developed into a resultative complement, an adverb, and an adjective is that of grammaticalization, while on the other hand, the process by which duàn developed into a noun is that of lexicalization. Essentially, it is the intransitive function that is subject to grammaticalization and it is the transitive function that is subject to lexicalization. In this paper it is therefore proposed that the above diachronic change is taken as a cline, and is put forward as follows: (a) grammaticalization and lexicalization are not distinct processes but rather happen to a lexeme more or less simultaneously; and (b) interrelationship between the two processes is orthogonal.